Construct Loss Accounting Practices By Pangsit Traders Based On Faith In God - Thalib, Mohamad Anwar; Budianto, Rahman; Mabunga, Vitriyani Dg; Kiayi, Siti Sarah; Miftah, Seyan Nur (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2023)
This study aims to construct loss accounting practices based on non-material values. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The study results show that dumpling traders apply a strategy by not changing the selling price, raising the selling price when the price of essential commodities rises, looking for a crowded place to trade, and implementing a flexible selling price. This practice of accounting for losses requires the values of patience, gratitude, and compassion. This value lives based on faith that God is in control of sustenance. The implication of this finding is to present a holistic concept of accounting for losses, which does not only consist of material but also emotional and spiritual values.